(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article talks about the role of women in internal affairs bodies and gender equality issues in Uzbekistan. Based on historical data, the author studied and analyzed specific aspects of the role of women in internal affairs bodies and issues of gender equality in Uzbekistan based on available scientific literature.